72PNovel technique of near-focus mode for accurate operation during endoscopic submucosal tunneling procedure: A two-center comparative study. (24th November 2019) - Peng, W; Fu, X
Abstract: Background: The working space in the submucosal tunnel of endoscopic submucosal tunnel technique (ESTT) is limited, and the visual field is obscure during close inspection or hemostasis. This retrospective study aimed to evaluate the efficacy and safety of a novel near-focus mode technique for accurate operation during the submucosal tunneling endoscopic procedure. Methods: A retrospective two-center study was designed. A total of 51 patients undergoing ESTT procedures with near-focus mode (n = 29) or traditional mode (n = 22) between February 2016 and May 2019 were included in this study. Data regarding the efficacy, complications, hospital stay period, and other parameters were recorded. Results: When using the near-focus mode during the ESTT procedure, it is convenient to acquire a clear image and accurate operation. The clinical success rate was 100% (29/29) in near-focus group, higher than that in traditional group (90.9%, 20/22), although the difference was not significant (P = 0.181). The adverse event occurred more frequently in traditional group (45.5%) compared to that in the near-focus group (17.2%, P = 0.036). Especially, the near-focus group exhibited a significantly lower rate of bleeding compared to that of the traditional group (0 vs 18.2%, P = 0.029). Furthermore, the mean hospital stay after procedure was shorter in near-focus group (5.7 days) than that in traditional group (6.7 days, P = 0.013). Conclusions: The visual field is more clearly exposed within submucosal tunneling by using near-focus mode than traditional procedures. The efficacy and safety of this novel technique was proved in our procedures. Legal entity responsible for the study: Xiangsheng Fu. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.